Hubungan Tingkat Pengetahuan Dan Sikap Petugas Kesehatan Igd Terhadap Tindakan Triage Berdasarkan Prioritas - Yanty - Gurning; Darwin - Karim; Misrawati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to find out relationship of knowledge and attitude of emergency room workers towards triage actions based on priority. Methodology on this research was a descriptive correlative with cross sectional approach. The study conducted in emergency room of Eka Hospital Pekanbaru with 32 respondents as the sample, which were doctors and nurses. The sampling method used was total sampling technique. The measuring instrument used was questionnaire that has been tested for validity and reliability, and also using the observation sheet. The analysis used are univariate and bivariate analysis by Chi-squared test. The result of this research indicates that majority of respondent’s knowledge of triage actions with priority was high based on 17 people (53,1%), majority of respondents attitude towards triage action with priority was positive based on 19 people (59,4%) and majority of the respondents implement triage actions with priority accordance with the procedure were 18 people (56,3%). The result showed that there was a relationship between knowledge and attitude of emergency room workers towards triage actions based on priority for the P value < 0,05 which is (0.036 < 0,05) and ( 0,006 < 0,05). Based on the result of this research, emergency room workers are expected to be able to conduct triage action based on priority to prevent further death and disability. Keywords: Attitude, knowledge, triage